2003
DOI: 10.1246/cl.2003.912
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Stannole Anion by Alkylation of Stannole Dianion

Abstract: Reaction of tert-butylchloride with the stannole dianion first and simply prepared by the reduction of 1,1,2,3,4,5-hexaphenylstannole with lithium in ether gave 1-tert-butylstannole anion which was characterized by 1H, 13C, 119Sn, and 7Li NMR spectra and whose reactivities were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Tbt-substituted trihalostannane was synthesized by the reaction of SnCl 4 with TbtLi. Tbt-and Dip-substituted stannane, Tbt(Dip)SnH 2 (3), was prepared by the nucleophilic displacement reaction of the Tbt-substituted trihalostannane using DipMgBr, followed by reduction with LiAlH 4 . Bromination reaction of 3 using Br 2 in ether afforded the corresponding dibromostannane 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tbt-substituted trihalostannane was synthesized by the reaction of SnCl 4 with TbtLi. Tbt-and Dip-substituted stannane, Tbt(Dip)SnH 2 (3), was prepared by the nucleophilic displacement reaction of the Tbt-substituted trihalostannane using DipMgBr, followed by reduction with LiAlH 4 . Bromination reaction of 3 using Br 2 in ether afforded the corresponding dibromostannane 4.…”
Section: Resultsmentioning
confidence: 99%
“…Saito and his co-workers have recently reported the spectroscopic observation of a stannole dianion. [3] Although Schmidt et al have proposed the formation of (C 6 H 5 ) 2 SnLi 2 in the reaction of (C 6 H 5 ) 2 SnCl 2 with 4 molar amounts of Li, [4,5] the yields of the trapping reactions are not high and the generation of dilithiodiphenylstannane was not evidenced by 119 Sn and 7 Li NMR spectroscopy. More recently, Egorov et al reported the 119 Sn and 13 C NMR studies of Et 2 SnLi 2 and (C 6 H 5 ) 2 SnLi 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[19] When 1 equiv. of tert-butyl chloride was added to a diethyl ether solution of the stannole dianion 3, the color of the reaction mixture changed from deep red to bright red.…”
Section: Alkylation Of Stannole Dianionmentioning
confidence: 99%
“…of tert-butyl chloride was added to a diethyl ether solution of the stannole dianion 3, the color of the reaction mixture changed from deep red to bright red. By treatment of the reaction mixture with methyl iodide, the 1-tert-butyl-1-methylstannole 15 [19] was obtained in 55 % yield, suggesting the formation of the stannole anion 16 bearing a tertbutyl group on the tin atom (Scheme 7). The formation of 16 from 3 is reasonably explained by an electron-transfer mechanism, as observed in the reaction of the tributylstannyl anion with tert-butyl halides.…”
Section: Alkylation Of Stannole Dianionmentioning
confidence: 99%
“…The chemistry of group 14 metallole dianions has been developed enormously [11,12], and recently the stannole dianion [SnC 4 Ph 4 ] 2− was also reported [13,14,15,16]. …”
Section: Introductionmentioning
confidence: 99%